Solution of six chemical engineering problems using the Chebyshev orthogonal collocation technique - Binous, Housam; Kaddeche, Slim; Bellagi, Ahmed (Computer applications in engineering education, 2017)
The Chebyshev orthogonal collocation is a powerful and accurate numerical technique, which is also relatively easy to implement using modern mathematical software (e.g., MATHEMATICA © and MATLAB ®). This technique allows the elucidation of engineering problems involving partial differentials equations or boundary value problems. Six chemical engineering problems concerning the transfer of momentum, heat, and mass, with varying degree of complexity, are elucidated. The results obtained using the subject numerical technique were systematically bench‐marked against the results derived from alternative approaches. Benchmarking indicates good agreement between the results, despite the simplicity of this technique. Thus, this technique has a great potential for the elucidation of problems, for which no known solutions exist.